STUDY OF THE QUALITY OF LIFE PATIENTS SUFFERING FROM NERVOUS DISEASES AT DIFFERENT AGE PERIODS IN RESEARCH - Atajanova Laylokhan Uktamovna (Journals Park Publishing, 2023)
The article provides information on the results of research conducted by foreign scientists on the quality of life of stroke patients at different ages.
Keywords: stroke, quality of life, depression, ischemic stroke, psychoemotional sphere, intellectual sphere, physical activity, neurology, apathy, cognitive disorders, memory.